Contemporary management of benign parotid tumours – the increasing evidence for extracapsular dissection. (11th July 2016) - Brennan, PA; Ammar, M; Matharu, J
Abstract : Benign parotid tumours have historically often been managed surgically by superficial parotidectomy. While this approach usually gives a generous cuff of surrounding normal parotid tissue to increase tumour margins, it requires a much larger incision than the increasingly used extracapsular dissection (ECD) technique. Furthermore, superficial parotidectomy can result in marked facial hollowing, Frey syndrome and an increased risk of both temporary and permanent facial nerve weakness. ECD has been popularised as a safe alternative to parotidectomy primarily for the removal of mobile, benign parotid tumours with safe outcomes and reduced risk to the facial nerve. In this article, we review the growing body of evidence for ECD and include our own experience confirming the move away from superficial parotidectomy in contemporary practice for the treatment of benign parotid tumours.